Uga3 and Uga35/Dal81 transcription factors regulate UGA4 transcription in response to γ-Aminobutyric acid and Leucine - Cardillo, S.B. (2010)
The Saccharomyces cerevisiae UGA4 gene encodes a permease capable of importing γ-aminobutyric acid (GABA) and δ-aminolevulinic acid (ALA) into the cell. GABA-dependent induction of this permease requires at least two positive-acting proteins, the specific factor Uga3 and the pleiotropic factor Uga35/Dal81. UGA4 is subjected to a very complex regulation, and its induction is affected by the presence of extracellular amino acids; this effect is mediated by the plasma membrane amino acid sensor SPS. Our results show that leucine affects UGA4 induction and that the SPS sensor and the downstream effectors Stp1 and Stp2 participate in this regulation. Moreover, we found that the Uga3 and Uga35/Dal81 transcription factors bind to the UGA4 promoter in a GABA-dependent manner and that this binding is impaired by the presence of leucine. We also found that the Leu3 transcription factor negatively regulates UGA4 transcription, although this seems to be through an indirect mechanism. © 2010, American Society for Microbiology.